2021
DOI: 10.1111/jace.17736
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of UO2 symmetric tilt grain boundaries around [001] axis

Abstract: Molecular dynamics and CRG empirical potential are used in this work to study the symmetrical tilt grain boundaries around the [001] axis in UO2. The analysis of atomic structures obtained by simulation shows excellent agreement with the Read and Schokley model (Read WT, Shockley W. Dislocation Models of Crystal Grain Boundaries. Physical Review. 1950;78:275) predicting the existence of regular dislocations in these grain boundaries. We calculated their energy of formation and cleavage as well as the energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(128 reference statements)
2
6
0
Order By: Relevance
“…In general, annealing leads to lower GB energies and a smaller fluctuation in the results. The good agreement between fitted and MD results indicates that the dislocation‐based BRK functions are applicable for UO 2 , which is consistant with a recent MD study that demonstrated the dislocation structures in UO 2 GBs 12 …”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…In general, annealing leads to lower GB energies and a smaller fluctuation in the results. The good agreement between fitted and MD results indicates that the dislocation‐based BRK functions are applicable for UO 2 , which is consistant with a recent MD study that demonstrated the dislocation structures in UO 2 GBs 12 …”
Section: Resultssupporting
confidence: 83%
“…The good agreement between fitted and MD results indicates that the dislocation-based BRK functions are applicable for UO 2 , which is consistant with a recent MD study that demonstrated the dislocation structures in UO 2 GBs. 12 The energies of three 2D GB sets, the <100>, <110>, and <111> ATGBs, are plotted in Figures 5 and 6 as functions of the misorientation angle, ξ, and the asymmetry angle, η. The energies of the ATGBs are fitted to Equation (5) for <100>, Equation ( 6) for <110>, and Equation ( 7) for <111>, respectively.…”
Section: D and 2d Gbs In Uomentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a positive correlation between GB thermal resistance and GB energy in CeO2, which is a commonly studied surrogate ceramic for UO2, has been suggested by molecular dynamics (MD) simulations [6]. Also, the cleavage energy for intergranular fracture in UO2 has been shown to decrease with increasing GB energy [11,12]. The percolation paths for gas release are likely comprised of high energy GBs which favor gas bubble nucleation and growth [13].…”
Section: Introductionmentioning
confidence: 98%